Efectos de las actividades antrópicas sobre parámetros metabólicos en un bivalvo invasor y otro nativo en el tramo inferior del río Paraná - Noya Abad, Tatiana; Peluso, Julieta; Minaberry, Yanina Susana; Rojas, Dante Emanuel; Cristos, Diego Sebastian; Knack De Almeida, Henrique; Yusseppone, María Soledad; Aronzon, Carolina Mariel; Calcagno, Javier Ángel; Sabatini, Sebastián Eduardo (Asociación Argentina de Ecología, 2022)
The relationship between anthropogenic contamination, geochemistry, and the natural dynamics of freshwater ecosystems determine spatial and temporal patterns of water quality. Human activities and the introduction of exotic species are main causes of the decline in biodiversity. The introduction and spread of the invasive bivalve Corbicula fluminea puts the presence of the native bivalve Diplodon delodontus at risk. With oxidative stress indicators, the responses of organisms to changes in physicochemical, natural or anthropogenic variables can be quantified. Our objective was to interpret the effect of changes in physicochemical, polluting or xenobiotic variables on the metabolic responses of C. fluminea and D. delodontus in the Paraná de las Palmas river. In September 2018, a sampling and collection point of individuals was randomly established (60 of the invasive bivalve and 10 of the native) to assemble 10 cages per species at the placement site. In June and September 2019, five cages per species were randomly extracted. In water Physicochemical and metal parameters were determined, and in the organs of both species, the concentration of proteins, glycogen, lipid damage, reduced glutathione content, enzymatic activity of catalase and glutathione-S-transferase. In general, the physicochemical and metal parameters increased significantly from June to September. The metals exceeded freshwater quality guideline levels to protect aquatic life. Regarding the changes in these variables, the metabolic parameters differed between organs and species from June to September. The gills and digestive glands of C. fluminea showed higher metabolic responses and in less time than D. delodontus. Studying an invasive species and a native one with measurements of multiple variables is useful to characterize the environment, in the case of water quality monitoring and conservation studies.